Конституційний суд України: питання удосконалення конституційно-правового регулювання - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2013)
The article is devoted to the issues of improvement of the constitutional and legal regulation as to the organization and activities of the Constitutional Court of Ukraine. The article provides the necessity of amending the Constitution of Ukraine and the Law of Ukraine «On the Constitutional Court of Ukraine» in order to increase the efficiency of the sole body of constitutional jurisdiction in Ukraine, which will enhance the effectiveness of mechanisms of the Constitution protection, ensuring the constitutional legality, protection of human rights and freedoms.
Крусян А. Р. Конституційний суд України: питання удосконалення конституційно-правового регулювання / А. Р. Крусян // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 22-31.
Keywords: Конституційний Суд України; правовий статус Конституційного Суду України; конституційне судочинство; конституційна скарга; конституційне провадження; рішення та висновки Конституційного Суду України; Конституционный Суд Украины; правовой статус Конституционного Суда Украины; конституционное судопроизводство; конституционная жалоба; конституционное производство; решения и заключения Конституционного Суда Украины; the Constitutional Court of Ukraine; the legal status of the Constitutional Court of Ukraine; the constitutional jurisdiction; the constitutional complaint; the constitutional proceedings; decisions and conclusions of the Constitutional Court of Ukraine